Eksplorasi Peran Bidan dan Dukungan Keluarga Dalam Mempromosikan Pemberian ASI Eksklusif di Puskesmas Indraloka Jaya Tahun 2025 - Marsya Soleha; Novita Novita (Universitas Pahlawan Tuanku Tambusai, 2025)
The reality that occurs in society is that breastfeeding is only a matter between the mother and baby, even though in reality there are many factors that influence the success of exclusive breastfeeding. One of the important factors that supports the success of exclusive breastfeeding is providing support to mothers both from the family and from health workers, especially midwives. Based on the background description above, the author is interested in conducting research with the title